Specificity of early-career general practitioners' problem formulations in patients presenting with dizziness: a cross-sectional analysis. Issue 4 (24th December 2021) - Ledger, Jocelyn; Tapley, Amanda; Levi, Christopher; Davey, Andrew; van Driel, Mieke; Holliday, Elizabeth G; Ball, Jean; Fielding, Alison; Spike, Neil; FitzGerald, Kristen; Magin, Parker
Abstract : Objectives: Dizziness is a common and challenging clinical presentation in general practice. Failure to determine specific aetiologies can lead to significant morbidity and mortality. We aimed to establish frequency and associations of general practitioner (GP) trainees' (registrars') specific vertigo provisional diagnoses and their non-specific symptomatic problem formulations. Design: A cross-sectional analysis of Registrar Clinical Encounters in Training (ReCEnT) cohort study data between 2010 and 2018. ReCEnT is an ongoing, prospective cohort study of registrars in general practice training in Australia. Data collection occurs once every 6 months midtraining term (for three terms) and entails recording details of 60 consecutive clinical consultations on hardcopy case report forms. The outcome factor was whether dizziness-related or vertigo-related presentations resulted in a specific vertigo provisional diagnosis versus a non-specific symptomatic problem formulation. Associations with patient, practice, registrar and consultation independent variables were assessed by univariate and multivariable logistic regression. Setting: Australian general practice training programme. The training is regionalised and delivered by regional training providers (RTPs) (2010–2015) and regional training organisations (RTOs) (2016–2018) across Australia (from five states and one territory). Participants: All general practice registrars enrolled with participating RTPs or RTOs undertaking GP training terms. Results: 2333 registrars (96% response rate) recorded 1734 new problems related to dizziness or vertigo. Of these, 546 (31.5%) involved a specific vertigo diagnosis and 1188 (68.5%) a non-specific symptom diagnosis. Variables associated with a non-specific symptom diagnosis on multivariable analysis were lower socioeconomic status of the practice location (OR 0.94 for each decile of disadvantage, 95% CIs 0.90 to 0.98) and longer consultation duration (OR 1.02, 95% CIs 1.00 to 1.04). A specific vertigo diagnosis was associated with performing a procedure (OR 0.52, 95% CIs 0.27 to 1.00), with some evidence for seeking information from a supervisor being associated with a non-specific symptom diagnosis (OR 1.39, 95% CIs 0.92 to 2.09; p=0.12). Conclusions: Australian GP registrars see dizzy patients as frequently as established GPs. The frequency and associations of a non-specific diagnosis are consistent with the acknowledged difficulty of making diagnoses in vertigo/dizziness presentations. Continuing emphasis on this area in GP training and encouragement of supervisor involvement in registrars' diagnostic processes is indicated.